Karakteristik Endapan Kuarter di Dataran Aluvial Rawa Utara Pangkalan Balai, Kabupaten Banyuasin (Sumsel) ( Suatu Studi Awal dari Efek Perubahan Iklim dalam Proses Sedimentasi) - Herman Moechtar (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The sediments in this area are of fluvial and swarnp systems, The fluvial deposits include channel sand, and fine grained cIay of floodplain deposits. The swarnp deposits of Iine-grained include humic clay and peaty clay, the basement of this Quaternary deposits is tufaceous clay of pyroclastic.The character of Quaternary depositional style at the PangkaIan Balai and surrounding is dominantly influenced by autogenic mechanisms (internal processes), such as river channel systems and sediment supply from the    surrounding hills.  The cIimate factor of allogenic rnechanisms (externaI processes) is specific to related humidity as chemicaI, physics, or biology aspects in time.Keywords: Fasies, fluvial and swamp, internal and external process.